Educating Boys in Jamaica: In Search of a New Lens - Chin, Marcia Sharon-May (University of San Diego, 2018)
The need for innovative solutions to enhance educational outcomes for Jamaican high school male students is evident. For over two decades, national exam results demonstrate that these students have consistently underachieved. Using a qualitative research design, this study explores the possibility of scaling up a student leadership educational model, developed by one U.S. school that has proven successful in educating an inner city minority male student population, to a similarly placed Jamaican high school. Focus groups and interviews were conducted with stakeholders at an all male Jamaican school and with administrators at the Ministry of Education, to understand their perceptions regarding the benefits, challenges and feasibility of the U.S. model for Jamaican high school male students. While participants’ attraction to the model was very strong, the possibility of transferring it was perceived to be low. Although Jamaican educators found aspects of the model helpful, they felt the need to construct their own model of education to respond to their contextual and cultural needs. This study offers two levels of analysis. First, it contributes on a macro level to the larger body of literature on scaling up educational reform, demonstrating the need to take into account the structural, cultural and agentive factors that co-construct and define the importance of context. This study shows that successful scaling up requires a high level of alignment with the educational goals, aspirations, beliefs, values and practices of the target school context. Second, this study contributes on a micro level to a greater understanding of the specificity of the Jamaican educational context. By examining the potential transferability of a student leadership educational model to help address high school male students’ academic underperformance, this study highlights how Jamaican educators’ deeply ingrained historical values, beliefs and practices, shape opportunities to reform education. In order to bring about meaningful change, successful transferability relies on sensitivity to school culture, as well as attending to stakeholders’ beliefs and practices regarding the education of male students.
Keywords: High school; Male students; Educating boys; Jamaica